Afterscripts of Malabar Migration: The Dalit Christian Standpoint and the Syrian Christian Question in Vinoy Thomas’s Karikkotakary (2014) - Joshwa, Jobson (The journal of religion & society, 2026)
Discursivities around migration have always shaped and defined the Kerala imaginary. Notwithstanding, there have not been any substantial engagements with Kerala’s rather deep history of internal migration. The Malabar migration that witnessed the large-scale movement of people from Travancore to British Malabar between the 1920s and 1970s is largely seen as a peasant migration incurred by the severe socio-economic conditions, including poverty and the Second World War. A notable specificity of the migration was the high composition of Syrian Christians among the peasants. To critically problematize this community specificity, this article closely analyses Vinoy Thomas’s novel Karikkotatakary (2014). This article argues that Malabar migration could be viewed as an instantiation of the Syrian Christian community’s assertion and contends further that Vinoy Thomas deploys Dalit Christianity as a critical pointer to respond to these latent historicities of Malabar migration, serving as a critique of Syrian Christian religiosity and community consciousness.